Perceived benefits and barriers towards exercise among healthcare providers in Ain Shams University Hospitals, Egypt - Hebat-Allah M. S. Gabal; Maha M. Wahdan; Waleed Salah Eldin (SpringerOpen, 2020)
Abstract Background Physical inactivity is considered a problem with great impact on morbidity and mortality. There is a necessity to combat this behavior through an assessment of barriers and benefits perceived by subjects. Objectives The current study aimed to measure exercise intention, in addition to identifying physical exercise predictors, including perceived barriers and benefits among healthcare providers (HCPs) in Ain Shams University Hospitals. Methods A cross-sectional study was performed on a sample (n = 327) of healthcare providers (physicians and nurses) in Ain Shams University Hospitals in Cairo, Egypt, using anonymous self-administrated questionnaires and relevant scales. Results Out of 327 healthcare providers approached, 52.6% of them were males and the mean age of participants was (29.34 ± 7.84 years). Physical exercise was reported by 44.6% of participants. The most significant factors associated with physical exercise engagement were male gender, participants with lower body mass index (BMI), and those with higher perceived "life enhancement subscale" benefit score and lower perceived exercise milieu and physical exertion barriers subscale scores. Exercisers showed significantly higher total overall (benefits and barriers) score compared to non-exercisers. Physicians showed a significantly higher total score compared to nurses. Conclusion and recommendations The prevalence of regular exercise is low and inversely related to the female gender, BMI, Exercise milieu, and Physical exertion barriers subscale scores, and directly related to life enhancement benefit subscale score. Health education program about the benefits and barriers of exercise is recommended to encourage healthcare personnel to follow a healthy lifestyle as a role model to their patients and to act as health promoters to them.